Role-play as a single methodological strategy for English language teaching - López Cruz, Ricardo Damián (2023)
English language teaching and learning has become a necessary and useful tool for people all over the world. Nonetheless, the process of teaching and learning English language is not always developed in a good way due to different factors such as economics, students' motivation and methodological strategies used by the teacher. This research is focused on analyzing the importance of role-play as a single methodological strategy in English language teaching and its influence on the development of communicative skills for teaching English in 10th EGB of the "Once de Noviembre" Educational Unit. For this research a descriptive design was applied, considering that the research topic has enough theoretical support. Likewise, this research was designed under a mixed approach because it adapts to its characteristics and needs. The techniques used for data collection were the survey and the interview questions, one of which was conducted with English teachers of the educational unit and the other with 10th grade students. From the mixed approach, the technique of interview questions will be used to analyze the teachers' opinion about role-play as the only strategy for English language teaching. In addition, a survey was applied to the students to know the aspects generated by the strategy. The study population consisted of fifteen students and three English teachers from the “Once de Noviembre” Educational Unit located in Latacunga city, Cotopaxi province. The results of this study showed that not all teachers knew about the use of role-play and its benefits. While the students stated that they liked learning through the role-play because they are dynamic activities and that their communicative skills had improved. Therefore, it is concluded that the use of role-play is of great importance for teaching of the English language as well as for the development of communicative skills such as speaking and listening. It also helped in the interaction and dynamics in class in students of 10th grade of the educational unit "Once de Noviembre".